Research on Operation Mechanism optimization framework of Power Grid Business Organization under the new circumstances. Issue 1 (April 2021) - Meng, Weixuan; Cheng, Jiaxu; Liu, Jin
Abstract: The construction of Energy Internet enterprises drives the deep coupling between external power supply service and internal specialty synergiztion of Power Grid Enterprises. Based on the situation of Energy Internet construction and the requirements of "strong front-end, big back-end" platformized organization mode, this paper explores and puts forward the framework of operation mechanism optimization of power grid business organization, which can provide reference for power grid enterprises to promote organizational reform.